Afrahat, Mowa XVII – O Chrystusie, Synu Bożym - Uciecha, Andrzej (Vox Patrum, 2020)
Demonstration On Christ, who is the Son of God is the seventeenth exposition in Aphrahat’s work. The Persian sage continues and develops his polemic against Judaism in general and the teachings of the rabbis of the Babylonian diaspora in particular. The truth about the divinity of Messiah, Christ, who fulfilled all the prophecies of the Old Testament, is a focal point of his whole argument. Aphrahat consequently refutes critique formulated by the Jews who accuse Christians of fraudulent interpretation of Old Testament prophecies and attributing a divine status to Jesus what they maintain a blasphemy. The demonstration is not a lengthy work. This fact raises a question if it is not the exact reason why Aphrahat, aware of the weakness of this argument on Jesus, Son of God, broke the literary conventions of acrostic and supplemented his work with the twenty-third demonstration, extensive Demonstratio de acino (On the Grapecluster).